Characterization of full tensor properties of single-domain tetragonal 0.63Pb(Mg1/3Nb2/3)O3–0.37PbTiO3 single crystal using only one sample. Issue 7 (May 2018) - Huo, Da; Wang, Qixiang; Lü, Weiming; Zheng, Limei; Lu, Xiaoyan; Liu, Jingshun; Jing, Yujia; Yang, Liya; Zhang, Rui
Abstract: Complete sets of piezoelectric, dielectric and elastic material constants are of great importance for both theoretical study and device design during applications. Usually several samples are needed to get the complete matrix properties. Property variation between different samples makes the obtained data difficult to achieve self-consistency. In this work, the combined pulse-echo ultrasound and inverse impedance spectroscopy method was adopted to determine the full tensor properties of [001]C –poled single domain 0.63Pb(Mg1/3 Nb2/3 )O3 –0.37PbTiO3 single crystals. By using this method, only one small sample was needed, therefore self-consistency was easily achieved. The final inversion results were proved to be stable by changing the initial values. In addition, the obtained full matrix data were compared to those measured by combined resonance and ultrasonic method, which showed that our method exhibited high accuracy. This unique method provides a powerful tool for the accurate characterization of piezoelectric materials, especially those are highly segregated or difficult to grow.